Epidemiological Uncertainty, Causation, and Drug Product Liability - Goldberg, Richard (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2014)
Epidemiological evidence is regularly presented to courts in determining proof of causation in medicinal product liability litigation. Building on the foundations of the author’s previous monograph, which supported the use of epidemiological evidence in dealing with problems of proof of causation in alleged cases of adverse drug reactions, this paper revisits this perennial problem of the role of epidemiological evidence in assessing causation in product liability cases in a twenty-first century context, examining recent cases in the United Kingdom, United States, Australia, and Canada. It seeks to determine the extent to which the courts in the highlighted cases have been pragmatic and fair in their interpretation and utilization of epidemiological evidence, from the perspective of both consumers and pharmaceutical manufacturers. The paper examines the apparent tension between the levels of proof required in law and science, including the relationship between levels of statistical significance and the claimant’s burden of proof; and it assesses the wisdom of using a doubling of the risk rule as a threshold to any recovery. It explores the ways in which probabilistic methods, including statistical refining with individual risk factors, can be used in conjunction with epidemiological evidence to determine specific causation. The paper supports the view that logistic regression techniques and other forms of statistical refining mechanisms using specific risk factors can and do help in the process of giving quantitative or quasi-quantitative expression to conclusions about the cause of disease in an individual drug product liability claim that is based on epidemiological evidence.